KAJIAN PENANGANAN BANJIR DENGAN SISTEM POMPA DI SUNGAI BENDUNG, KOTA PALEMBANG - Heru Gunawan; Anis Saggaf; Sarino . (JURNAL SUMBER DAYA AIR, 2021)
Floods around the Bendung River in Palembang City have caused material and non-material losses. One of the reasons was the decreasing river capacity and backwater during the Musi River flood season, which is the Bendung River's outlet. This paper discusses the impact of adding a pump system to reduce flood impact. 1-dimensional and 2-dimensional numerical model using MIKE 11 and MIKE FLOOD were made to analyze the best measures. Various alternative scenarios were implemented in the model. Based on the modeling results, using the most optimal alternative, alternative 4 with 6 pumps of 36 m3/s and normalization of the Bendung River channel by 1 meter. The inundation area was reduced by 0.74 km2. Also, the maximum inundation height for the flood decreased by 0.6 meters, and the inundation duration was reduced by 8.5 hours. These modeling results can be a reference for managers and policymakers in managing flood events.Keywords: River channel normalization, pump system, numerical model, flood control, Bendung river